Diseño y elaboración de talleres de cultura y ahorro en los padres de familia para mejorar el bienvivir de los niños de primer año de educación básica paralelo “b” de la escuela mixta “Abdón calderón “ubicada en la parroquia Alàquez del cantón Latacunga en la provincia de Cotopaxi durante el año lectivo 2010 – 2011. - Loma Lasluisa, Rosa del Pilar (2014)
Within the teaching-learning process is important to determine the cognitive needs of the educational community, therefore, within the research is classified three chapters with content relating to the culture of saving. The methodology for the development of descriptive research is allowing us to meet the needs that the educational community of the savings, then, if applicable processions constructivist teaching-learning process is innovative results which will enable the student in this case parents, formed in a balanced way on issues of savings workshops. The chapter includes a literature review and netgráfica for describing the fundamental categories relating to savings and design within the educational community. The information content of survey data collection and channeled it through the chapters number two which allows for the needs and realities of education of the savings by the parents. The third chapter focuses directly on the proposal of two workshops at rates governed andragogical a systematic planning and content.